PENGARUH KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA DIVISI TELEOPERATION PT BFI FINANCE INDONESIATBK BSD SERPONG - Rosalinda Harahap; Henni Marlinah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to determine the impact of leadership and work motivation on employee performance at PT BFI Finance Indonesia TBK BSD Serpong, both partially and simultaneously. The research method used in this study is quantitative research. The population used in this study were employees of PT BFI Finance Indonesia TBK BSD Serpong. The sampling method used by the author in this study is the Slovin method, where the sample was 140 employees of PT BFI Finance Indonesia TBK BSD Serpong. The data collection method used in this study is primary data. The primary data taken were data from the answers of 140 respondents. Data analysis used validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, autocorrelation tests, multiple linear regression tests, and simple linear regression tests, correlation coefficient analysis, determination coefficient tests, partial hypothesis tests (t-tests), and simultaneous hypothesis tests (f-tests). The results of this study are that leadership and work motivation simultaneously have a significant effect on employee performance with the regression equation Y = 13.249 + 0.828 X1 + 0.746 X2. Leadership has a significant effect on employee performance with a determination coefficient value of 75.3% and the hypothesis test obtained a calculated t value > t table value or (20.485 > 1.977). Leadership has a significant effect on employee performance with a determination coefficient value of 83.5% and the hypothesis test obtained a calculated t value > t table value or (19.569 > 1.977). The determination coefficient value is 89.4% while the remaining 10.6% is influenced by other factors. The hypothesis test obtained a calculated F value > F table or (42.951 > 2.671).